It’s 10077 because it’s hey
Ok, this definition of f is just a bunch of points (4 to be exact).
so if point (a,b) is part of f, then f(a)=b
f(1) is about point (1,0), so f(1)=0.
g(1) = 1 (due to point (1,1))
g(2/3) = 0
f(2) = 3/4
g(-2) = 3
f(π) = -2
just a lookup once you see what is happening
I run 1 mile every 6 minutes.
My friend runs 1 mile every 7 minutes.
Lowest Common Multiple: LCM ( 6, 7 ) = 42 minutes.
Me : 42 : 6 = 7 miles
My friend : 42 : 7 = 6 miles.
Answer:
B (5, 13)
Step-by-step explanation:
9x + 4y = 97
9x + 6y = 123
To solve by elimination, we want to <em>eliminate</em> a variable. To do this, we must make one variable cancel out.
First, we can see that both equations have 9x. To cancel out x, we must make <em>one</em> of the 9x's <em>negative</em>. To do this, multiply <em>each term</em> in the equation by -1.
-1(9x + 6y = 123)
-9x - 6y = -123
This is one of your equations. Set it up with your other given equation.
9x + 4y = 97
-9x - 6y = -123
Imagine this is one equation. Since every term is negative, you will be subtracting each term.
9x + 4y = 97
-9x - 6y = -123
___________
0x -2y = -26
-2y = -26
To isolate y further, divide both sides by -2.
y = 13
Now, to find x, plug y back into one of the original equations.
9x + 4(13) = 97
Multiply.
9x + 52 = 97
Subtract.
9x = 45
Divide.
x = 5
Check your answer by plugging both variables into the equation you have not used yet.
-9(5) - 6(13) = -123
-45 - 78 = -123
-123 = -123
Your answer is correct!
(5, 13)
Hope this helps!
The answer is f^-1(x)=8/3+x/3